2007
DOI: 10.1016/j.brainres.2007.01.131
|View full text |Cite
|
Sign up to set email alerts
|

Nrf2-mediated protection against 6-hydroxydopamine

Abstract: Parkinson's disease (PD) is a neurodegenerative movement disorder characterized by cell loss in the substantia nigra resulting in striatal dopamine depletion. Although the cause of sporadic PD is unknown, oxidative stress is thought to contribute to disease pathogenesis. One mechanism by which cells defend themselves against oxidative stress is through the transcriptional upregulation of cytoprotective genes. Under oxidative stress conditions, the transcription factor NF-E2-related factor (Nrf2) binds to the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
165
1
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 220 publications
(174 citation statements)
references
References 55 publications
(64 reference statements)
7
165
1
1
Order By: Relevance
“…Two asterisks mark P<0. Nrf-2 activators protects DA neurons from the neurotoxicity of 6-OHDA in vivo (63) and in rat organotypic nigrostriatal cocultures (64). These results collectively suggest that astrocytes are involved in antioxidant signaling both in vivo and in vitro.…”
Section: Reactive Astrocytes In Pdmentioning
confidence: 66%
“…Two asterisks mark P<0. Nrf-2 activators protects DA neurons from the neurotoxicity of 6-OHDA in vivo (63) and in rat organotypic nigrostriatal cocultures (64). These results collectively suggest that astrocytes are involved in antioxidant signaling both in vivo and in vitro.…”
Section: Reactive Astrocytes In Pdmentioning
confidence: 66%
“…8 significant protection to neurons in vivo. [28][29][30][31] Chemical/ drugs that activate this pathway may have efficacy in blocking neuronal cell death. A focused effort to find those that cross the blood-brain barrier efficiently, activate the pathway in astrocytes, and have efficacy against neurotoxicity is underway.…”
Section: Discussionmentioning
confidence: 99%
“…6-OHDA stimulates the production of superoxide radicals and induces cell death (8). Numerous experiments have revealed that antioxidants exert beneficial effects in the prevention of 6-OHDA-induced cytotoxicity (9,10).…”
Section: Introductionmentioning
confidence: 99%